Desapego emocional en la niñez y su repercusión en la salud mental de una joven de 22 años del cantón Babahoyo - Suarez Sanchez, Ruben Dario (2022)
The purpose of this case study or research is to analyze emotional detachment in childhood and its impact on the mental health of a 22-year-old girl from Babahoyo Canton, in which fundamental tools and techniques were applied to obtain a reliable diagnosis based on to the symptomatology of the patient that manifested in the first session or psychological attention, therefore, to obtain information, the initial interview is applied, in which personal data is known, reason for consultation, the frame is made, and it is sent homework, on the other hand there is direct observation, which allowed us to understand the patient's body language through tone of voice, movements, body state, gestures among others, consequently the clinical history is applied, which is detailed in detail from the root, that is, from childhood to the present age, and finally the complementary tests called psychometric tests, which resulted in the cie 10 in the Z codes, Loss of affective relationship in childhood Z61.0, structural diagnosis that facilitated the realization of the therapeutic scheme through Cognitive Behavioral Therapy, for the modification of negative thoughts for positive ones, control and regulation of emotions, strengthening security, self-esteem, reintegration with the family and social environment and raising awareness of emotional dependence due to lack of affection since childhood.